2020
DOI: 10.18176/jiaci.0391
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Omalizumab in Severe Allergic Asthma and Nasal Polyposis: A Real-Life Study

Abstract: Background: Omalizumab is a human anti-IgE antibody approved for the treatment of severe allergic asthma (SAA). However, its effectiveness in SAA associated with chronic rhinosinusitis with nasal polyposis (CRSNP+) is less well documented. Objective: The aim of this study was to evaluate the real-life effectiveness of omalizumab in patients with SAA and CRSNP+ who tolerated and did not tolerate aspirin. Methods: We performed a retrospective, observational, multicenter, real-life study of patients with SAA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 32 publications
4
38
0
Order By: Relevance
“…Our findings are in line with those recently reported by Tiotiu et al in a retrospective, multicenter study that included patients with severe allergic asthma and CRSwNP treated with omalizumab for 6 months [40 ]. They observed an improvement in all lower airways clinical outcomes in this particular subgroup of patients with severe asthma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with those recently reported by Tiotiu et al in a retrospective, multicenter study that included patients with severe allergic asthma and CRSwNP treated with omalizumab for 6 months [40 ]. They observed an improvement in all lower airways clinical outcomes in this particular subgroup of patients with severe asthma.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of omalizumab in patients with severe allergic asthma associated with CRSwNP may suggest a possible concomitant effect of the drug on nasal polyps outcomes, as previously shown [40, 47 ]. The efficacy of omalizumab in patients with CRSwNP, with or without asthma, was recently confirmed in two phase III studies (POLYP 1 [48 ] and POLYP 2 [49 ]), where omalizumab met both co‐primary endpoints and multiple key secondary endpoints, showing significant improvements in health‐related quality of life, smell, congestion, endoscopic nasal polyp size, post‐nasal drip, and runny nose [50 ].…”
Section: Discussionmentioning
confidence: 63%
“… 38 Two additional case series also demonstrate improvement in patient reported olfaction, which did not reach statistical significance. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“… AERD-ASA: 10.0 → 6.3∗ AERD-placebo: 8.0 → 8.4 ATA - ASA: 8.2 → 8.0 ATA - placebo: 6.5 → 8.3 Ibrahim et al 32 ASA (325–650 mg Bid) Case series 111 Patient reported improvement in smell: yes/no Post ASA improvement: 34/111 (30.6%) Sweet et al 33 ASA 650 mg Bid (average) Cohort AERD + Placebo (Control): 42 AERD + discontinued ASA: 30 AERD + ASA long term: 35 Patient reported olfactory dysfunction: interval scale 1–5 1 = perfect smell 5 = complete anosmia Change in score at follow-up Control: −0.1 Long term ASA: −1.2∗ Short term ASA: −1.3∗ → +0.5 after d/c Rozsasi et al 34 ASA 100 mg vs. ASA 300 mg Cohort ASA 100 mg: 7 ASA 300 mg: 7 Sniffin' Sticks odor identification range: 0–12 Difference c (12 mo. Post ASA Score - Baseline) 300 mg: −3∗ 100 mg: +1 Monoclonal antibodies Laidlaw et al 35 Dupilumab Cohort; double blinded placebo controlled Control (AERD): 11 Dupilumab: 8 UPSIT + SNOT-22 Smell Subscore >50% reduction post Dupilumab at 4 mo.∗ (numerical data not published) Philips-Angles et al 36 Omalizumab Case series 7 Visual analog scale range: 0–4 Olfactory improvement in 5/7 (71%) at 6 months b Tiotiu et al 37 Omalizumab Case Series AERD: 9 Visual analog scale range: 0–10 Baseline → Post Omalizumab (6 mo.) 8.67 ± 1.33 → 5.44 ± 2.62∗ Hayashi et al 38 Omalizumab Case Series 21 Visual analog scale range: 0–10 Baseline → Post Omalizumab (12 mo.)…”
Section: Introductionmentioning
confidence: 99%
“…Despite some discordant published data regarding the effects of omalizumab on lung function (15), many real-life studies have shown that this anti-IgE monoclonal antibody can induce significant and persistent increases in forced expiratory volume in the first second (FEV 1 ), lasting 5, 7, and even 9 years (94-96). Moreover, it was also recently reported that omalizumab can effectively improve both clinical manifestations and computed tomography (CT) images of nasal polyps associated with severe allergic asthma (97). All these beneficial outcomes achieved by patients undergoing add-on therapy with omalizumab explain the high degree of adherence to this biologic drug (98).…”
Section: Licensed Biological Therapies Of Severe Asthmamentioning
confidence: 97%